Transmissibility of Mycobacterium pinnipedii in a murine model - Marfil, María Jimena (2024)
The causative agent of tuberculosis in pinnipeds is Mycobacterium pinnipedii, amember of the Mycobacterium tuberculosis complex (MTC). The natural hosts arepinnipeds; however, other non-marine mammals, including humans, can also beinfected. The transmissibility of a pathogen is related to its virulence. Thetransmissibility of a M. pinnipedii strain (i.e., 1856) was investigated in a murinemodel and compared with that of two Mycobacterium bovis strains (i.e., 534 and04-303) with different reported virulence. Non-inoculated mice (sentinels) wereco-housed with intratracheally inoculated mice. Detailed inspection of mice tosearch for visible tuberculosis lesions in the lungs and spleen was performed, andbacillus viability at 30, 60, and 90 days post-inoculation (dpi) was assayed. Atransmissibility of 100% was recorded at 30 dpi in sentinel mice co-housed withthe inoculated mice from the M. pinnipedii and M. bovis 04-303 groups, asevidenced by the recovery of viable M. pinnipedii and M. bovis from the lungs ofsentinel mice. Mice inoculated with M. pinnipedii (1856) and M. bovis (534) surviveduntil euthanized, whereas five of the M. bovis 04-303-inoculated mice died at 17dpi. This study constitutes the first report of the transmissibility of a M. pinnipediistrain in mice and confirms the utility of this experimental model to study virulencefeatures such as the transmission of poorly characterized MTC species.